Pelatihan Penerapan Sistem Informasi Pendataan Obat Pada Praktek Mandiri Bidan Supiani - Iwan Fitrianto Rahmad; Budi Triandi; Ratih Puspasari; Lili Tanti (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
The drug data collection information system is an application used in medical services, where with the use of a drug data collection system, drug data will be stored and arranged neatly for a long time, then with the use of this system it reduces file storage costs and minimizes file storage space. Prior to the use of this drug data collection system, the midwife supiani clinic was given to record drugs by recording on a patient biographical paper in which the patient's history of treatment and type of illness will be stored on the paper. The manual system causes complications in the services provided to patients, because patients will wait very long because the administration will search and unload data if the patient has visited or been treated, if it is the first time you want to seek treatment, the administration must look for serial numbers and record names. patient data and patient biodata, causing quite a long time in the administration process. With the drug data collection information system provided at the general practice of midwives, it is very helpful in terms of data recording, file storage and so that services for patients become faster and more efficient. One more thing, the general practitioner midwife supiani can recapitulate in one day any drugs that are reduced. This is a very large contribution to the general practice of midwives so that they can improve patient treatment services. The results of the evaluation after being given training increased after being given training and assistance in training on the use of the drug data collection information system developed by the Team, which was 88.75%. These results indicate that the increase in knowledge and skills of activity participants after participating in a series of activities is in the